ANALISIS RISIKO: LANGKAH STRATEGIS UNTUK MENCEGAH KERUGIAN DAN MENINGKATKAN PROFITABILITAS SUATU PERUSAHAAN. (STUDI KASUS: PERKEMBANGAN PARIWISATA DI KOTA MEDAN) - Arsyadona; Devi Tri Saputri Manik; Fahira Rizka Olivia Mahyu; Widya Ananda; Syahril Ramadhan Hasibuan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article explains the importance of risk analysis on the strategic basis of a business to prevent losses and increase profitability. This article also explains strategic steps in risk management, from systematic risk identification and assessment to implementing effective risk reduction strategies. This article also analyzes the application of risk management in tourism management, with a case study of tourism development in Medan City. Risk management is a crucial aspect in developing tourism management to minimize negative impacts that may arise and ensure the sustainability of the tourism sector. Medan has quite large tourism potential with 26 tourist attractions spread throughout the city, but faces challenges in terms of security, accessibility and less than optimal promotion. This discussion covers the various risk analysis techniques involved and how to integrate effective risk management into a company's strategic decision making. In this analysis, the risk management approach will be evaluated based on a SWOT strategy that identifies strengths, weaknesses, opportunities and threats to increase the effectiveness of tourism management. The goal is to provide practical guidance to companies on how to build strong risk management systems to achieve sustainability and sustainable growth. This article also highlights the importance of integrating risk management into strategic decision making, showing how a proactive approach to risk can ensure organizations are prepared for a variety of unexpected scenarios.